Pengaruh Penggunaan Media Pop-Up Book Terhadap Tingkat Penguasaan Kosakata Anak Usia 4-5 Tahun di TK Efrata Medan T.A 2024/2025 - Kristin Agustina Simatupang; Dorlince Simatupang (Institut Nalanda, 2024)
The problem in this study is the level of vocabulary mastery of children is lacking in terms of pronouncing animal names, plants, and recognizing colors. 1) It was found that 6-8 children out of a total of 16 children in class A Kindergarten had difficulty speaking or communicating because children had difficulty developing vocabulary or composing words into sentences that were easy for others to understand, especially teachers. 2) It was found that around 6-8 children could only pronounce 100-300 words in a day. 3) It was found that around 7-8 children had insufficient vocabulary such as vocabulary for names of objects, colors, animals, plants and also recognizing numbers. This study aims to determine the influence of Pop up Book media on the level of vocabulary mastery of children aged 4-5 years in Efrata Kindergarten. The population of this study was all children aged 4-5 years in Class A Efrata Kindergarten totaling 15 children.